3(2x-5)+4(x+2)=-7

Simple and best practice solution for 3(2x-5)+4(x+2)=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-5)+4(x+2)=-7 equation:


Simplifying
3(2x + -5) + 4(x + 2) = -7

Reorder the terms:
3(-5 + 2x) + 4(x + 2) = -7
(-5 * 3 + 2x * 3) + 4(x + 2) = -7
(-15 + 6x) + 4(x + 2) = -7

Reorder the terms:
-15 + 6x + 4(2 + x) = -7
-15 + 6x + (2 * 4 + x * 4) = -7
-15 + 6x + (8 + 4x) = -7

Reorder the terms:
-15 + 8 + 6x + 4x = -7

Combine like terms: -15 + 8 = -7
-7 + 6x + 4x = -7

Combine like terms: 6x + 4x = 10x
-7 + 10x = -7

Add '7' to each side of the equation.
-7 + 7 + 10x = -7 + 7

Combine like terms: -7 + 7 = 0
0 + 10x = -7 + 7
10x = -7 + 7

Combine like terms: -7 + 7 = 0
10x = 0

Solving
10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '10'.
x = 0.0

Simplifying
x = 0.0

See similar equations:

| x^5-2x^4-8x^3=0 | | 2(x+4)=38-4x | | 6v+32=-6+8(v+4) | | -5/8=g-1/4 | | 0.6x=28.3 | | -6(4n-6)-2n=-7n+17 | | y-4=6 | | h+4/9=7/9 | | 7.4+d=-18.62 | | m-9.78=65.32 | | 6.3+k=12.5 | | b/4+10=13 | | 16+2a=-2(3a-4) | | 11-4x=6+x | | 4c+0=48 | | 3g-1+2g+8=g+2 | | A=5i+7j | | u+6=v | | -5+3x+3+2= | | -2(7-4)+4=-4 | | 7a=15a-80 | | 15y-12y=24 | | 0.02=100 | | 20y^7v^8u^2= | | 3(-2+x)=-24 | | 2b-6-3b-b= | | 10+7x=5x-6 | | (2x-1)(x+3)=(x-3)(x+1) | | 3x+21=68 | | -72-11c+6c^2=0 | | -4-5=3-3x+4x | | -2x-1=-(2x+3) |

Equations solver categories